Extract of the bioconverted fine root of ginseng induces apoptosis and cell cycle arrest in mouse colon cancer cells - Yeonju Seo; Jongbeom Chae; Ju-Ock Nam (Applied Biological Chemistry, 2023)
Abstract Cancer is the major cause of death worldwide, and the anticancer effect of ginseng and its main root has been studied. However, study of fine root of ginseng (FRG) is still insufficient. The purpose of this study was to discover a new anticancer effect from FRG, which does not show an anticancer effect, through a bioconversion technique. We measured and compared cell viability in FRG- and bioconverted fine root of ginseng (BFRG)-stimulated CT26 cells to investigate differences caused by bioconversion. Cell viability of CT26 was suppressed upon treatment with BFRG, unlike FRG. The effect of BFRG on apoptosis and cell cycle arrest was investigated by flow cytometry. BFRG-stimulated CT26 cells showed an increased apoptotic cells and cell cycle arrest. Additionally, BFRG induced mitochondrial impairment by reducing the expression of anti-apoptosis protein Bcl-2. When confirming the signaling pathway, it was found that the p38 MAPK pathway was activated by BFRG. Collectively, our results reveal anticancer effects against colorectal cancer and represent potential targets for anticancer drug development.